Hepatic cells derived from human skin progenitors show a typical phospholipidotic response upon exposure to amiodarone. (1st March 2018) - Natale, Alessandra; Boeckmans, Joost; Desmae, Terry; De Boe, Veerle; De Kock, Joery; Vanhaecke, Tamara; Rogiers, Vera; Rodrigues, Robim M.
Highlights: Human skin-derived hepatic cells (hSKP-HPC) show drug-induced phospholipidosis (DIPL) in vitro . Amiodarone induces accumulation of intracellular phospholipids and formation of typical lamellar bodies in hSKP-HPC. Amiodarone modulation of phospholipidosis-related genes is much stronger in hSKP-HPC then in HepG2 cells. hSKP-HPC represent a useful in vitro model to screen for phospholipidogenic compounds. Abstract: Phospholipidosis is a metabolic disorder characterized by intracellular accumulation of phospholipids. It can be caused by short-term or chronic exposure to cationic amphiphilic drugs (CADs). These compounds bind to phospholipids, leading to inhibition of their degradation and consequently to their accumulation in lysosomes. Drug-induced phospholipidosis (DIPL) is frequently at the basis of discontinuation of drug development and post-market drug withdrawal. Therefore, reliable human-relevant in vitro models must be developed to speed up the identification of compounds that are potential inducers of phospholipidosis. Here, hepatic cells derived from human skin (hSKP-HPC) were evaluated as an in vitro model for DIPL. These cells were exposed over time to amiodarone, a CAD known to induce phospholipidosis in humans. Transmission electron microscopy revealed the formation of the typical lamellar inclusions in the cell cytoplasm. Increase of phospholipids was already detected after 24 h exposure to amiodarone, whereas a significant increase of neutral lipid vesicles could be observed after 72 h. At the transcriptional level, the modulation of genes involved in DIPL was detected. These results provide a valuable indication of the applicability of hSKP-HPC for the quick assessment of drug-induced phospholipidosis in vitro, early in the drug development process.